Towards the Empowerment of Waqf Based on Community Needs in the Mentawai Islands West Sumatra: The Case of the Al-Qur'an Wakaf Board - Tiswarni, Tiswarni; Hidayat, Rahmat; Novia, Aidil; Jayusman, Jayusman; Hadi, Sutrisno; Alfadhli, Alfadhli (Fakultas Syariah UINSI Samarinda, 2023)
This article explains the utilization of Al-Qur'an and Development Waqf (WAP waqf) and clean water waqf through the Al-Qur'an Waqf Board in the Mentawai Islands, which is based on the basic needs of the community in the religious and social fields. This waqf was motivated by the backwardness of the people in the Mentawai Islands from a religious and social perspective, which prompted the Al-Qur'an Waqf Board to allocate waqf programs there. Research data was collected through in-depth interviews and documentation. It was then analyzed descriptively and qualitatively. The research findings show that the Al-Qur'an Waqf Board allocates Al-Qur'an accompanied by guidance to the Mentawai Muslim community as waqf. The utilization form of WAP waqf for Mentawai Islands people provides broad access to studying and understanding the Al-Qur'an, coaching daily worship, coaching and mentoring new converts to Islam, and coaching preachers before preaching to the community. The utilization of the water waqf is in the form of building clean water facilities in mosques and near residential areas, accompanied by religious and sanitation development for the communities receiving the waqf benefits. These findings can have implications for the importance of understanding the main problems of society so that the utilization of waqf can be more diverse and provide maximum benefits. The utilization of waqf must address the basic needs of society so that it can solve problems that develop in society while still relying on sharia.